Are There Any Differences in the Continuous Usage Intention of E-Wallet Users?: The Case of Seoul and Jakarta - Nusraningrum, Dewi; Yuniarsih, Retno (UUM Press, 2024)
The unstoppable use of the Internet, especially in big cities, has led to changes in payment patterns and financial transactions. Originally, wallets have transitioned to electronic wallets, driven by perceived benefits, ease of use, and social influence among e-wallet users. Therefore, it is crucial to investigate the intention to continuously use e-wallets among young people who have become accustomed to Internet usage. The method employed for processing the data collected through questionnaires is SEM-PLS. The research sample consisted of 240 young e-wallet users in Seoul and Jakarta who participated in the study. The results showed a discrepancy in the effect of perceived ease of use on the continuous usage intention of e-wallets among the young users in the two cities. Young users in Seoul found e-wallets easy to use, whereas users in Jakarta perceived the opposite. However, the perceived usefulness and social influence had a positive and significant effect on the continuous usage intention of e-wallets in both cities. This indicates that Generation Z believes e-wallets will continue to be used due to their benefits and the influence of social factors. This implication underscores the penetration of Internet users and mobile applications associated with e-wallet users. The findings of this research hold significant importance for the rapidly expanding e-wallet industry today, serving as a valuable reference for the development of the e-wallet market